Konsep Komunikasi Dalam Perspektif Al-Qur’an Studi Kasus Manajemen Pendidikan Islam Di Sekolah - Abdul Malik; Ahmad Zubair Rudianto; Muh. Bahrul Afif (STAIN MAJENE, 2025)
This research aims to analyze the concept of communication in the Al-Qur'an, especially those contained in Q.S. An-Nahl verse 125, Q.S. An-Nisa verses 9 and 63, Q.S. Al-Ahzab verse 32, Q.S. Al-Isra verse 23, as well as Q.S. Thoha verse 44, and applying it to the management of Islamic education. The focus of the study is to explore Islamic communication principles that can be applied in building a harmonious, ethical and effective educational environment. The research method used is library research with a thematic interpretation approach. These verses are analyzed to identify Islamic communication values ​​such as wisdom, empathy, politeness and respect. The data collected comes from tafsir books, Islamic education literature, and other relevant research. The research results show that each verse makes an important contribution in forming communication strategies in Islamic education management. Q.S. An-Nahl verse 125 emphasizes a wise approach, polite dialogue and good advice, which are relevant in guiding students. Q.S. An-Nisa verses 9 and 63 emphasize empathy and gentleness in communication, which helps create harmonious relationships between educators, students and other stakeholders. Q.S. Al-Ahzab verse 32 teaches the importance of maintaining politeness in social interactions, especially between genders, which can be applied in communication ethics in educational environments. Q.S. Al-Isra verse 23 teaches respect in communication, especially towards authority figures such as teachers and parents. Meanwhile, Q.S. Thoha verse 44 emphasizes gentleness in conveying messages even in difficult situations, which is relevant in handling conflicts in educational institutions